The Burden of Human Metapneumovirus (hMPV) Disease in Older and High-Risk Adults in Developed Countries: A Systematic Literature Review - Ajoke Sobanjo-ter Meulen; Aura V. Gutierrez; Ornella Ruiz; Jennifer Eeuwijk; Hilde Vroling; Niranjan Kanesa-thasan (Infectious Diseases and Therapy)
Abstract Introduction Human metapneumovirus (hMPV) causes respiratory infections in individuals of all age groups. While the evidence on hMPV epidemiology is growing, the hMPV burden in adults has not been synthesised. We conducted a critical review of published evidence on the burden of hMPV in older adults and adults with comorbidities. Methods Articles reporting the burden of hMPV disease in adults ⩾50 years or ⩾18 years with comorbidities in developed countries were searched in Embase and MEDLINE (1/January/2000–12/June/2023) databases. Observational and interventional studies on community-based or medically attended populations were included. Outcomes of interest encompassed prevalence, incidence, clinical presentation, severe outcomes and complications, healthcare utilisation, coinfection with respiratory syncytial virus or influenza, and child-to-adult transmission. We assessed the risk of bias, performed a qualitative and quantitative synthesis, and calculated pooled estimates using random-effects meta-analysis (PROSPERO: CRD42023439068). Results In total, 119 of 2847 articles met the inclusion criteria, covering 663,361 patients. hMPV accounted for 3.4% (95% confidence interval [CI] 2.7–4.2%, I 2 = 66%) of annual and 4.0% (95% CI 2.9–5.3%, I 2 = 78%) of seasonal symptomatic respiratory infections in older adults and 4.3% (95% CI 3.2–5.7%, I 2 = 66%, annual) and 5.1% (95% CI 3.2–7.9%, I 2 = 82%, seasonal) in high-risk adults. For high-risk adults, the estimated proportion of hMPV cases requiring hospitalisation was 51.4% (95% CI 33.2–69.3%, I 2 = 46%). Among medically attended cases, the proportions admitted to the intensive care unit and those resulting in mortality were 6.6% (95% CI 4.8–9.1%, I 2 = 34%) and 9.3% (95% CI 4.6–18%, I 2 = 0%), respectively. Conclusions hMPV burden is substantial in the adult population, particularly among those with underlying diseases. Limited evidence exists in community settings, alongside the lack of routine testing for hMPV, which hinders the estimation of the actual burden of hMPV. These findings underscore the need for tailored prevention and treatment strategies for hMPV infection, such as vaccination or antiviral treatments.